Biomaterials : principles and applications - Park, Joon Bu; Bronzino, Joseph D. (CRC Press, 2002)
Metallic biomaterials - Ceramic biomaterials - Polymeric biomaterials - Composite biomaterials - Biodegradable polymeric biomaterials: an updated overview - Biologic biomaterials: tissue derived biomaterials (collagen) - Soft tissue replacements - Hard tissue replacements - Preservation techniques for biomaterials - Hip joint prosthesis fixation: problems and possible solutions.